Strengthening Family Health Through Koenih Rimbo Cultivation and Cancer Prevention Education in the Ikhwatunnisa Padang Women's Farmer Group - Filza Yulina Ade; Benny Alexander Maisa; Carbiriena Solusia; Zuhrah Taufiqa; Dwi Hilda Putri; Chelsylia Dara Pratama (Pelita Eksakta, 2026)
Cancer is one of the leading causes of death worldwide, yet medical treatments remain costly and often cause side effects. Herbal-based alternatives are increasingly relevant, including the use of Curcuma sumatrana (koenih rimbo), an endemic plant from West Sumatra with anticancer potential. This community service program aimed to enhance the knowledge of the Ikhwatunnisa Women Farmers Group on cancer prevention, early detection, and the sustainable cultivation of koenih rimbo. The activities involved three stages: socialization, health education, and training in conservation and cultivation. Results showed a significant improvement in participants’ knowledge, with understanding of cancer risk factors and early detection rising from 30% to 80%. Participants also showed enthusiasm in cultivating koenih rimbo, viewing it as a way to support family health while conserving biodiversity. This program demonstrates the importance of integrating health education and plant conservation to empower local communities, particularly women farmers, in achieving sustainable development goals.